2023
DOI: 10.3390/app13137513
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Levitation Belt Conveyor Control System Based on Multi-Sensor Fusion

Abstract: Belt conveyors are critical in coal transportation systems; however, they are supported by rollers, which incur high energy costs. Magnetic levitation support is adopted. The measurement of a magnetic levitation air gap is important, and a displacement sensor is usually used in real-time. To address the problems of poor linearity and low measurement stability of single displacement sensors in magnetic levitation systems, a magnetic levitation support system based on multi-sensor data fusion is proposed. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recently, magnetic levitation (MagLev) systems have been extensively researched for transporting logistics in various manufacturing plants as well as traditional transportation methods such as trains [1][2][3][4]. The studied MagLev systems are being considered to replace the existing belt-type conveyor system in the semiconductor and OLED display panel production process [3][4][5][6][7]. These processes require a highly clean environment because fine dust has a significant impact on production yield [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, magnetic levitation (MagLev) systems have been extensively researched for transporting logistics in various manufacturing plants as well as traditional transportation methods such as trains [1][2][3][4]. The studied MagLev systems are being considered to replace the existing belt-type conveyor system in the semiconductor and OLED display panel production process [3][4][5][6][7]. These processes require a highly clean environment because fine dust has a significant impact on production yield [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in semiconductor manufacturing processes, the development of contactless delivery systems has been actively developed due to the importance of particle-free and highly accurate delivery operations [3][4][5][6]. Magnetic levitation technology is considered a highly promising alternative to meet these requirements [7].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a schematic diagram of the environment. The empirical data revealed that conveyor belt system had been a focus of numerous studies in terms of researching the actual amount of material on belt [4][5][6], tracking the movements [7][8][9], checking for product quality, detecting faults, speed regulation strategy and variable belt-speed energy issue for energy saving [10], etc. These researches discuss various techniques for extracting the material from the belt through computer vision techniques, such as background subtraction, canny edge detection, and morphological operations for analysis and quantification of the material to perform further processes on it to achieve their desired goals [4].…”
Section: Introductionmentioning
confidence: 99%